GOOGLE EARTH TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN GEOGRAFI KELAS XII DI SMA ADABIAH PADANG - Mawaddah, Nurul; Mariya, Sri (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This research aims to analyze the influence learning model of the Problem Based Learning using Google Earth media on the learning outcomes of geography lessons for Adabiah Padang High School Students. In this reseaech, a quantitative approach was used using a quasi experimental type with samples taken randomly. Hypothesis testing using the t-test and a significance level of 0.05 produces ’count ≥ ’rabelnamely 11.435 > 1.67155, so Ha is accepted and H0 is rejected. Thus, there is an influence of the Problem Based Learning model using Google Earth media on learning outcomes of geography students at Adabiah Padang High School.